2015
DOI: 10.4102/curationis.v38i2.1510
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the affordances of mobile devices in integrating theory and clinical practice in an undergraduate nursing programme

Abstract: BackgroundPromoting the quality and effectiveness of nursing education is an important factor, given the increased demand for nursing professionals. It is important to establish learning environments that provide personalised guidance and feedback to students about their practical skills and application of their theoretical knowledge.ObjectiveTo explore and describe the knowledge and points of view of students and educators about introduction of new technologies into an undergraduate nursing programme.MethodTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 17 publications
2
22
0
8
Order By: Relevance
“…Accordingly, many studies emphasised the affordances of MIM to provide instantaneous learning communications stressing an added value, which is rather logistic than pedagogic ( (Bere, 2012, p. 10). This was deemed to be particularly important in work-based learning settings, where learners received immediate advice from their tutors in solving more complex problems (Willemse & Bozalek, 2015). The mixed-method case study of Rambe and Bere (2013b) emphasised the use of MIM to provide South African IT students with prompt feedback in question-based consultations from peers and lecturers, which helped them solve problems and discuss academic issues.…”
Section: Immediacy Versus Delays: Timing Communicationmentioning
confidence: 99%
See 4 more Smart Citations
“…Accordingly, many studies emphasised the affordances of MIM to provide instantaneous learning communications stressing an added value, which is rather logistic than pedagogic ( (Bere, 2012, p. 10). This was deemed to be particularly important in work-based learning settings, where learners received immediate advice from their tutors in solving more complex problems (Willemse & Bozalek, 2015). The mixed-method case study of Rambe and Bere (2013b) emphasised the use of MIM to provide South African IT students with prompt feedback in question-based consultations from peers and lecturers, which helped them solve problems and discuss academic issues.…”
Section: Immediacy Versus Delays: Timing Communicationmentioning
confidence: 99%
“…In opposition to intimacy, users and educators also perceived the use of MIM as an intrusion into their personal lives. While intrusive communication patterns did not present a burden to all users -as one educator commented, "I allowed my private space to be invaded but I did not mind" (Ramukumba, 2015, p. 8) -many studies revealed users' need for detachment from increasingly ubiquitous learning communities (Aburezeq & Ishtaiwa, 2013;Bere, 2012;Bouhnik & Deshen, 2014;Rambe & Bere, 2013a;Smit, 2015;So, 2016;Willemse & Bozalek, 2015). One reason that triggered users' needs for detachment were discussions that reached into time they perceived as personal.…”
Section: Intimacy Versus Detachment: Negotiating Social Relationshipsmentioning
confidence: 99%
See 3 more Smart Citations